Informacion en hecho y derecho de don Luis Coronel Luna, olim don Pedro Luis Ladron. En el articulo de nulidades dichas por don Francisco Ladron marques de Terranova - España - Alegaciones en derecho; Coronel Luna, Luis; Luis Steve, Pedro; Mey, Pedro Patricio (1609)
Valencia, en casa de Pedro Patricio Mey, 1609. Citation confidence: An exemplar has been referenced in a major analytical bibliography, or inspected book in hand, by a member of the Iberian Books project team or a collaborating institution. Citation/reference: IB: 30666